D-q equivalent circuit-based protection algorithm for a doubly-fed induction generator in the time domain. - Yong-Cheol Kang (Journal of electrical engineering & technology)
Most modern wind turbines employ a doubly-fed induction generator (DFIG) system due to its many advantages, such as variable speed operation, relatively high efficiency, and small converter size. The DFIG system uses a wound rotor induction machine so that the magnetizing current of the generator can be fed from both the stator and the rotor. We propose a protection algorithm for a DFIG based on a d-q equivalentcircuit in the time domain. In the DFIG, the voltages and currents of the rotor side and the stator side are available. The proposed algorithm estimates the instantaneous induced voltages of magnetizing inductance using those voltages and currents from both the stator and the rotor side. If the difference between the two estimated induced voltages exceeds the threshold, the proposed algorithm detects an internal faults. The performance of the proposed algorithm is verified under various operating and fault conditions using a PSCAD?EMTDC simulator